2008
DOI: 10.1097/jom.0b013e3181845fb1
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Carpal Tunnel Syndrome and Median Neuropathy in a Working Population

Abstract: ., "Risk factors for carpal tunnel syndrome and median neuropathy in a working population". Journal of Occupational and Environmental Medicine, 50, 12, 1355-1364. 2008. Methods: A cross-sectional assessment of 1108 workers from 8 employers and 3 unions completed nerve conduction testing, physical exam, and questionnaires. CTS was defined by median neuropathy and associated symptoms.Results: Eighteen workers had CTS and 131 had evidence of median neuropathy. CTS was highest among construction workers (3.0%) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 38 publications
4
60
0
5
Order By: Relevance
“…Any significant orders [22]. In another study, Armstrong et al reported that CTS, epicondylitis and tendinitis were frequently observed among hairdressers [7]. In this study, we have detected that the CTS frequency among hairdressers is higher than for the control group composed of unemployed participants.…”
Section: Boston Carpal Tunnel Syndrome Questionnaire (Bctsq) [8]supporting
confidence: 39%
See 1 more Smart Citation
“…Any significant orders [22]. In another study, Armstrong et al reported that CTS, epicondylitis and tendinitis were frequently observed among hairdressers [7]. In this study, we have detected that the CTS frequency among hairdressers is higher than for the control group composed of unemployed participants.…”
Section: Boston Carpal Tunnel Syndrome Questionnaire (Bctsq) [8]supporting
confidence: 39%
“…Hairdressing is associated with using some devices and techniques which are believed to precipitate the several health problems like CTS, tendinitis and epicondylitis. It is reported that prevalence of CTS for hairdressers is higher as compared to the rest of the society due to the usage of scissors and other tools for a long time [7]. To the best of our knowledge, there is limited information regarding the relation of CTS and hairdressers in our community.…”
Section: Nerve Conduction Studiesmentioning
confidence: 68%
“…The incidence of reported CTS in the general population of Olmstead County, Minnesota, from 2000-2005 was 4.4 per 10 000 and the average incidence of work-related CTS surgery was 1.1 per 10 000 (3). The prevalence of electrodiagnostically confirmed CTS from employee computer use and among active workers in healthcare and construction was 1.7% (4). The incidence of CTS confirmed with nerve conduction studies in the general Dutch and Italian populations varied between 1.8-2.8 per 1000 in 2001 (5,6).…”
mentioning
confidence: 96%
“…This property has led to use of computerized EDX instrumentation in multicenter drug registration trials 12 and large-scale epidemiologic studies. 13,14 Further, because of inherent consistency, the accuracy of the results as assessed in controlled clinical studies should translate to clinical practice. Diagnostic accuracy, with traditional EDX instrumentation or neuroimaging (for radiculopathy) as reference standards, has been reported for carpal tunnel syndrome, [15][16][17] upper-extremity nerve function in symptomatic patients, 18 -20 diabetic peripheral neuropathy, 21,22 lumbosacral radiculopathy, [23][24][25][26] and lower-extremity nerve function in symptomatic patients.…”
Section: Conflict Of Interestmentioning
confidence: 99%